Investigating requirements change requests - Gonçalves, Eduardo dos Santos; Malcher, Paulo; Antonino, Pablo Oliveira; Santos, Rodrigo Pereira dos (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: Software development is a highly dynamic, collaborative, and constantly changing process. Hence, the efficient management of requirements change requests (RCR) is essential to avoid negative impacts such as delays and quality compromise. Problem: The management of RCR in software development demands an understanding of associated motivator factors, solutions, and challenges. Solution: In this study, we aim to identify factors, solutions, and challenges in RCR management. IS Theory: This study is motivated by socio-technical theory, which addresses the technical and social aspects of requirements management. It highlights the interplay between stakeholder collaboration and technical processes in effectively managing RCR. Method: Employing the rapid review of the literature (RR) method, the research analyzes 37 selected studies from a traditional scientific database in the field of computing for this purpose—out of 1,061 retrieved results. Summary Results: The research reveals 19 factors (e.g., change in users/clients needs), 35 solutions (e.g., COSMIC Functional Size Measurement), and 12 challenges (e.g., time and resource consumption), providing a comprehensive overview of the RCR management landscape in software development. Contributions to IS: This study contributes to understanding factors, solutions, and challenges for managing RCR in software development. For academia, it contributes to disseminating knowledge about RCR, which contributes to advancing the state of the art of requirements change management. For the industry, it assists professionals in identifying, adopting, and implementing effective strategies to face the challenges in the area.